Relationships between brain structure-function coupling in normal aging and cognition: A cross-ethnicity population-based study - Liu, Chang; Jing, Jing; Jiang, Jiyang; Wen, Wei; Zhu, Wanlin; Li, Zixiao; Pan, Yuesong; Cai, Xueli; Liu, Hao; Zhou, Yijun; Meng, Xia; Zhang, Jicong; et al. (NeuroImage (Orlando, Fla.), 2024)
•A new index was developed to quantify brain SC-FC coupling and assess network topological similarity.•Cortical SC-FC coupling was strongest in the visual network and weakest in the ventral attention network.•In the cortex, SC-FC coupling strength declines with age and positively correlates with cognitive function. Increased efforts in neuroscience seek to understand how macro-anatomical and physiological connectomes cooperatively work to generate cognitive behaviors. However, the structure-function coupling characteristics in normal aging individuals remain unclear. Here, we developed an index, the Coupling in Brain Structural connectome and Functional connectome (C-BSF) index, to quantify regional structure-function coupling in a large community-based cohort. C-BSF used diffusion tensor imaging (DTI) and resting-state functional magnetic resonance imaging (fMRI) data from the Polyvascular Evaluation for Cognitive Impairment and Vascular Events study (PRECISE) cohort (2007 individuals, age: 61.15 ± 6.49 years) and the Sydney Memory and Ageing Study (MAS) cohort (254 individuals, age: 83.45 ± 4.33 years). We observed that structure-function coupling was the strongest in the visual network and the weakest in the ventral attention network. We also observed that the weaker structure-function coupling was associated with increased age and worse cognitive level of the participant. Meanwhile, the structure-function coupling in the visual network was associated with the visuospatial performance and partially mediated the connections between age and the visuospatial function. This work contributes to our understanding of the underlying brain mechanisms by which aging affects cognition and also help establish early diagnosis and treatment approaches for neurological diseases in the elderly.